(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Part of inhabitants of Panevezys, living in the city and near LiUdyne municipal waste landfill, still consumes water from dug wells. The aim was to investigate whether they are much polluted by toxic chemical elements and what is the main reason of their pollution. Geochemical monitoring data of dug wells in 3 industrial and 2 residential districts, as well as near LiUdyne municipal waste landfill were used. Water samples were analysed by AAS for V, Co, Ni, Cr, Cu, Pb, while sediment samples - by DC arc ES and XRF for total content of wider spectrum o f elements and by AAS for speciation o f the above mentioned 6 elements. Water quality was controlled in comparison with limit values of water for consuming, while the danger o f sediment pollution - according to recommended total contamination index levels for sediments and hygienic norms for mobile forms in soil. Sediments from dug wells can be effectively used as indirect inditator of their water pollution over longer period. Contamination from point sources in Panevezys is not the main reason of dug well pollution, the leading role belongs to local pollution in their sanitary zones. Therefore good care must be taken o f them.